2021
DOI: 10.1016/j.jcjd.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Diabetes Telemedicine Clinics for Aboriginal First Nation People With Reported Diabetes in British Columbia

Abstract: First Nations peoples in Canada often face geographic, social and cultural barriers to accessing diabetes care. Diabetes care requires mutual provider-patient understandings, strong relationships and continuity of care. Care that includes screening for complications, assessment of disease status and education can be provided by diabetes nurse educators with telemedicine specialist backup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…us, early screening and diagnosis are of great significance. e high blood glucose of diabetic patients with traumatic calcaneal fractures may retard fracture healing, and the patients are predisposed to postoperative complications such as incisional infections, which compromise the recovery of foot function and the quality of life of the patients [1][2][3]. It has been suggested that the combination of perioperative targeted therapeutic interventions contributes to reducing postoperative complications and shortening the recovery time [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…us, early screening and diagnosis are of great significance. e high blood glucose of diabetic patients with traumatic calcaneal fractures may retard fracture healing, and the patients are predisposed to postoperative complications such as incisional infections, which compromise the recovery of foot function and the quality of life of the patients [1][2][3]. It has been suggested that the combination of perioperative targeted therapeutic interventions contributes to reducing postoperative complications and shortening the recovery time [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The glycated hemoglobin and other risk factors were better controlled in this model than in non-Indigenous control groups. 4 The success was attributable in part to empowerment, cultural safety, and tracking of outcomes data. Broader social determinants continue to wield significant influence.…”
Section: Frame Of Referencementioning
confidence: 99%
“…The diabetes outcomes were better in this community than in control communities with programs delivered by primary care. 4 The key was a shared solution design and culturally enriched practices.…”
mentioning
confidence: 99%
“…In this issue of the Canadian Journal of Diabetes , 2 articles highlight the importance of expanding the reach of care systems to achieve equitable access to chronic disease care and care that acknowledges the historic harms and systemic racism that have impacted the health of Indigenous peoples. Dawson et al report on the health benefits of a multidisciplinary diabetes telemedicine clinic with expanded reach to rural and remote First Nations communities, which has engaged community members through trust, respect and relationship building ( 2 ). With mobile clinics reaching more than 60 communities and engaging approximately 99% of individuals known to have diabetes, programmatic screening, health education and promotion resulted in stabilization of glycated hemoglobin and body weight, and improvements in attaining blood pressure and lipid targets.…”
Section: Virtual Care In Chronic Illnessmentioning
confidence: 99%
“…However, it will also introduce new barriers related to technology, connectivity, communication and relationship building that risk perpetuating care inequities. As highlighted by Dawson et al ( 2 ) and Locke et al ( 3 ), partnerships with patients and communities will be key to moving forward. Through partnership, we can advance toward a health system that combines the strengths of virtual and in-person care to overcome prepandemic barriers to accessing health care for a postpandemic world.…”
Section: Health Care Post-covid-19mentioning
confidence: 99%